Prevalence of Behavioral and Psychological Symptoms of Dementia in Community-Dwelling Dementia Patients: A Systematic Review - Kwon, Chan-Young; Lee, Boram (Frontiers in Psychiatry, 2021)
Background: Identifying the characteristics of behavioral and psychological symptoms of dementia (BPSD) associated with different dementia types may be a promising strategy to effectively deal with BPSD. We aimed to synthesize the prevalence rates of BPSD characteristics in community-dwelling dementia patients. Methods: We searched Medline, EMBASE, and PsycARTICLES databases for original clinical studies published until December 2020 that enrolled at least 300 community-dwelling dementia patients. The methodological qualities of prevalence studies were assessed using the Joanna Briggs Institute’s critical appraisal checklist. Results: Thirty studies were included. The prevalence of the BPSD characteristic ranged from 4 (elation & mania) to 32% (apathy) in the pooled samples. The prevalence of delusions, anxiety, apathy, irritability, elation & mania, and aberrant motor behavior in Alzheimer's disease patients was 1.72 to 2.88 times greater than that in vascular dementia (VD) patients, while the prevalence of disinhibition in VD patients was 1.38 times greater. The prevalence of anxiety, irritability, and agitation & aggression, delusion, hallucinations, apathy, disinhibition, and aberrant motor behavior tended to increase as the severity of dementia increased, while that of depression, eating disorder, sleep disorders, and elation & mania tended to stable. In community-dwelling patients with dementia, the pooled prevalence of apathy, depression, anxiety, irritability, agitation & aggression, sleep disorders, and eating disorder was higher than 20%, while that of disinhibition and elation & mania was lower than 10%. Conclusion: Overall, the pooled prevalence of apathy, depression, anxiety, irritability, agitation & aggression, sleep disorders, and eating disorder was generally high in patients with dementia. Also, the prevalence of some BPSD characteristics differed according to the type and the severity of dementia. The methodological quality of the included studies is not the best, and high heterogeneity may affect the certainty of the findings. However, the results of this review can deepen our understanding of the prevalence of BPSD.